NONGKRONG ESTETIK DAN KEBUTUHAN SOSIAL STUDI TREN DI KALANGAN MAHASISWA ILKOM FISIP UNILA (Kohesi: Jurnal Sains dan Teknologi, 2025)
This study aims to analyze the application of the principles of openness, transparency, and accessibility in the management of funds for non-profit organizations, focusing on the Bani Chozin El Kafa Foundation in Pasuruan Regency. These principles are an important part of good governance in non-profit organizations that are social in nature and not profit-oriented. This research uses a qualitative approach with an interpretive method. Data was collected through in-depth interviews, participatory observation, and document analysis involving the foundation's management and guardians of students as primary informants. The results show that the foundation is quite good at implementing openness and transparency, although the implementation has not yet been fully optimal. Financial information has not been fully published proactively, and access to information is still limited to certain meeting forums. This study recommends strengthening human resource capacity, the application of information technology in reporting, as well as the creation of digital platforms to support transparency and accessibility.